Natural Reduction of Graphene Oxide to Graphene Using Kaffir Lime Leaves Extract - Chan, Bun Hoo; Willy Wong, Xiu Fa; Geraldine Chan, Sue Ching; Chong, Fui Chin (2014)
Previous research has proven that the reduction of graphene from graphene oxide successful via chemical reduction method with hydrazine and dextran; thermal reduction and also vitamin C. In this paper, the natural reduction of graphene from graphene oxide is presented by means of natural reduction to obtain higher reduction rate. The graphene was prepared via modified Hummer’s method due to its ability to produce graphene in large quantity. Graphite oxidizes to produce graphite oxide, then synthesizes to graphene oxide. Then, graphene oxide is reduced through natural reduction by using kaffir lime leaves extract. Optimization of the reductant (Kaffir Lime Extract) to produce highest reduction rate was done through the use of a parameter of retention time and concentration. The effectiveness of the reduction process was verified by Ultraviolet-visible spectroscopy (UV-Vis ) and the morphology of reduced graphene oxide was identified by using SEM (Scanning Electron Microscope ).